Identifikasi Penerapan Produksi Bersih di Industri Keripik Singkong - Shafira Viana Febriyanti; Utin Mahdiyah; Ayu Afifa Maharani; Dian Rahayu Jati; Isna Apriani (G-Tech: Jurnal Teknologi Terapan, 2023)
The industrial production process of cassava chips does not only produce positive value products but can be detrimental to the environment if not processed. This negative impact can be reduced through the implementation of cleaner production. The study aimed to conceptualize the application of clean production in the cassava chip industry, to determine the efficiency of implementing clean production in the cassava chip industry in reducing environmental pollution, and to determine the efficiency of implementing clean production in the cassava chip industry in improving the people's economy. The application of clean products in the Cassava Chips Industry, namely: (a) utilization of cassava peels as activated carbon generates a profit of Rp. (d) the use of wood pellets as a substitute for firewood, so that the profit if applying net production is IDR 294,000 per production. The application of cleaner production will have a good impact and be environmentally friendly.